A cross-cultural perspective on televised political advertising during the presidential election between the US and South Korea: 1992–2012. Issue 2 (3rd March 2016) - Lee, Soobum; Khang, Hyoungkoo; Kim, Yeojin
ABSTRACT: Our study was motivated by the fact that, despite the increasing pervasiveness of political advertising in the political process of many democracies, little empirical research has been conducted to unveil common patterns or crucial differences of political spots across cultural boundaries. Our study thus provided one opportunity to gain better understanding and insights into how media phenomena are related to cultural orientation by comparing and contrasting the content of political spots across the United States and South Korea. In particular, this study analyzed verbal components of political spots in both US and Korean presidential elections over the past 20 years. To the extent that clear differences exist between American and Korean cultural patterns, political spots, which are a conspicuous indicator of cultural values, appear to manifest these differences quite strongly. The findings of this study provide evidence that political advertising primarily reflects the uniqueness of indigenous cultures.